An Incidental Finding of Ecchordosis Physaliphora in a Case of Abducens Nerve Palsy: Case Report. (4th July 2018) - Ilorah, Chike; Bond, Brandon; Kattah, Jorge C.; Hassanzadeh, Bahareh
ABSTRACT: Ecchordosis physaliphora (EP) is a rare non-malignant mass that originates from remains of the notochord and is typically asymptomatic. A 42-year-old man presented with sudden onset of painless horizontal diplopia and his neurological exam showed sixth cranial nerve palsy. Magnetic resonance imaging (MRI) identified a non-enhanced retroclival mass (EP) with increased signal intensity on T2 and decreased signal intensity on T1-weighted sequences. He was treated with methylprednisolone, completely recovered in four weeks and has remained symptom free. Conservative management should be attempted before surgery in all cases since symptoms can resolve spontaneously and EP could be an incidental finding.